Arboreal forage lichen response to partial cutting of high elevation mountain caribou range in the Quesnel Higland of east-central British Columbia - Waterhouse, Michaela J.; Armleder, Harold M.; Linnell Nemec, Amanda F. (Rangifer, 2007)
Group selection silvicultural systems have been recommended for managing mountain caribou (Rangifer tarandus caribou) habitat in high elevation Engelmann spruce – subalpine fir forests in east-central British Columbia. We measured the response of arboreal lichen (a key winter forage) to harvesting of 30% of the forested area using three partial cutting treatments, which created small (0.03 ha), medium (0.13 ha), and large (1.0 ha) openings, and a no-harvest treatment. Treatments were replicated on four sites, and monitored over a ten year post-harvest period. The short-term loss of lichen associated with removal of approximately one third of the trees was partially offset by a significant (P=0.01) increase in lichen abundance on trees in the caribou feeding zone (up to 4.5 m) in the three partial cutting treatments relative to trees in the uncut forest. Differences among treatments in the change in lichen composition, as measured by the percentage of Alectoria sarmentosa and Bryoria spp., were marginally significant (P=0.10). The partial cutting treatments showing a greater likelihood of shifting towards more Bryoria spp. than no-harvest treatment (P=0.04). In the year of harvest (1993), larger trees were found to hold more lichen than smaller trees (P=0.04), and live trees supported more lichen than dead trees (P=0.01), but lichen loading was similar among tree species (P=0.51). Tree fall rates were similar among treatments, based on the ten year average (0.6–0.8% of sample trees per year). The results indicate that caribou foraging habitat is maintained in the residual forest when group selection systems that remove only 30% of the trees are applied. Information on the distribution of lichen is useful for developing stand level prescriptions. Providing lichen bearing habitat meets just one of the needs of caribou. A comprehensive approach that considers all factors and their interactions is essential to maintain and recover the threatened mountain caribou.